Healing starts with understanding: Addressing language barriers in patient care through medical student interpreters - Ji, Xinyu; Abdelhamid, Kenzy; Naumova, Darya; Chow, Ellen; Chirgwin, Juan-Carlos (McGill Journal of Medicine, 2020)
-